Influence of Marketing Capability on the Performance of Pharmaceutical Companies in Kenya - Okok, Meshack; Deya, Jared; Rotich, Gladys (European Journal of Business and Strategic Management, 2024)
Purpose: The main objective of the study is to assess the effects of marketing capability on the performance of pharmaceutical companies in Kenya. Methodology: The population comprised the 415 pharmaceutical companies that are operating within the country. The study used stratified random sampling with sample size of 103 respondents. The study targeted both manufacturers and distributors. Primary and secondary data was collected using a questionnaire covering the five variables and background information. The data was entered in SPSS version 23.0 for further analysis, descriptive statistics was computed such that the study used mean, frequencies, percentages and inferential statistics to test the relationship between the study variables. Findings: The correlation analysis revealed that there was a positive and significant association between marketing capability and firm performance (r = 0.608, p = 0.000). Regression of coefficients results revealed that marketing capability and firm performance are positively and significantly related (Î² =0.758, p=0.000). This implies that a unit increase in marketing capability would lead to increase in firm performance by 0.758. This implies that marketing capability significantly and positively influences performance of pharmaceutical companies in Kenya. Through marketing strategies, a firm is able to arouse interest of a customer to their products. It is concluded that the pharmaceuticals in Kenya have employed various marketing strategies that necessitate extension of pharmaceutical market hence improving performance. Unique Contribution to Theory, Practice and Policy: The study recommended the pharmaceutical company's management should embrace modern techniques of marketing to ensure they promote the sale of their products. The firms should prioritize customers' feedback to adequately fulfil their orders. Pharmaceutical companies should also embrace uniqueness in branding and quality to form a unique selling point for the company to arouse interest of the customer in the market.